The Silk Roads : a new history of the world - Frankopan, Peter. frey50 (New York Alfred Knopf, 2015)
"Our world was made on and by the Silk Roads. For millennia it was here that East and West encountered each other through trade and conquest, leading to the spread of ideas and cultures, the birth of the world's great religions, the appetites for foreign goods that drove economies and the growth of nations. From the first cities in Mesopotamia to the growth of Greece and Rome to the depredations by the Mongols and the Black Death to the Great Game and the fall of Communism, the fate of the West has always been inextricably linked to the East. The Silk Roads vividly captures the importance of the networks that crisscrossed the spine of Asia and linked the Atlantic with the Pacific, the Mediterranean with India, America with the Persian Gulf. By way of events as disparate as the American Revolution and the horrific world wars of the twentieth century, Peter Frankopan realigns the world, orientating us eastwards, and illuminating how even the rise of the West 500 years ago resulted from its efforts to gain access to and control these Eurasian trading networks. In an increasingly globalized planet, where current events in Asia and the Middle East dominate the world's attention, this magnificent work of history is very much a work of our times"--
The creation of the silk road -- The road of faiths -- The road to a Christian East -- The road to revolution -- The road to concord -- The road of furs -- The slave road -- The road to heaven -- The road to hell -- The road of death and destruction -- The road of gold -- The road of silver -- The road to Northern Europe -- The road to empire -- The road to crisis -- The road to war -- The road of black gold -- The road to compromise -- The wheat road -- The road to genocide -- The road of cold warfare -- The American silk road -- The road of superpower rivalry -- The road to catastrophe -- The road to tragedy -- Conclusion: The new silk road.
"This is a Borzoi book"--Title page verso.
Keywords: World history; Trade routes -- History; East and West -- History; Imperialism -- History; Culture conflict -- History; Acculturation -- History; HISTORY / World; HISTORY / Civilization; TRAVEL / Asia / China; Trade routes; Silk Road -- History; Asia -- Silk Road; History